Cost-utility analysis of genetic screening in families of patients with germline MUTYH mutations - Vasen Hans FA; Hes Frederik J; Nielsen Maartje; van den Hout Wilbert B (BMC, 2007)
Abstract Background MUTYH associated polyposis (MAP) is an autosomal recessive inherited disorder. Carriers of bi-allelic MUTYH germline mutations have a risk of approximately 60% to develop colorectal carcinoma (CRC). In the general population about 1.5% is a heterozygous MUTYH mutation carrier. Children of MAP patients have an increased risk of inheriting two MUTYH mutations compared to the general population, implicating an increased risk for developing CRC. Methods Using data from the literature and Dutch MAP patients (n = 40), we constructed a Markov model to perform a societal cost-utility analysis of genetic screening in MAP families. Genetic screening was done by testing the spouse first and, in case of a heterozygous spouse, also testing of the children. Results The cost of genetic screening of families of MAP patients, when compared to no genetic screening, was estimated at €25,000 per quality-adjusted life year (QALY). The presence of Fecal Occult Blood testing (FOBT) population screening only slightly increased this cost-utility ratio to €25,500 per QALY. For a MUTYH heterozygote index-patient, the ratio was €51,500 per QALY. The results of our analysis were sensitive to several of the parameters in the model, including the cost assumed for molecular genetic testing. Conclusion The costs per QALY of genetic screening in families of MAP patients are acceptable according to international standards. Therefore, genetic testing of spouses and/or children should be discussed with and offered to counselees.